GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 568514324 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false. The dataset includes 568514324 records from 12154 constituent datasets: 195 records from (Table 1) Planktonic foraminifera preservation indexes of ODP Hole 130-805C. 1683 records from Dinoflagellate cyst abundances at DSDP Site 94-607 from the North Atlantic (Appendix B). 1211 records from CSIRO, Cruise SS199101, Marine Biology Data, Western Australia, 1991. 24 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB04 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 34 records from Occurrence of mammalia relicts at site Nikolaushöhle. 96 records from Planktic foraminifera abundance of Hole 32-305. 24239 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 6035 records from Inland Fisheries Ireland data on freshwater fish in Irish lakes. 2 records from Gymnothorax hansi, a new species of moray eel (Teleostei: Anguilliformes: Muraenidae) from the Comoro Islands, Western Indian Ocean.. 496 records from Macroinvertebrate abundance in montane tropical streams of varying land-use, Ecuador. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 50000 records from observe_tuna_bycatch_ecoscope. 32 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D2. 584 records from Planktic foraminifera abundance of Hole 11-98. 600 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 518 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 8715 records from Ophiuroidea collections of the Zoological Institute Russian Academy of Sciences. 92344 records from Butterflies - Irish Butterfly Monitoring Scheme. 156283 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 19 records from (Table T3) Calcareous nannofossil abundance of ODP Hole 189-1170A sediments. 192 records from Range table from planktonic foraminifers in ODP Hole 146-891B. 4 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 182 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 8736 records from Naturhistorisches Museum Mainz, Zoological Collection. 40 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 9730 records from Royal British Columbia Museum Entomology Collection. 68076 records from CNIN/Lepidoptera. 977 records from Gurgltal (Tarrenz). 553 records from Planktic foraminifera abundance of Hole 68-503A. 108 records from Phytoplankton abundance off Chao island in Juli 2003, Peru. 1 records from Pollen analysis of sediment core FEL2, Felchowsee, Germany. 2126 records from HAS-Algae - Coleção Ficológica do HAS. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 10862 records from Heteroptera of Ireland. 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 131 records from Total foraminifera counts from multinet M31/2_MSN887. 124 records from Total foraminifera counts of multinet SO118_MSN1267. 205 records from Total foraminifera counts from multinet SO119_MSN1281. 48 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1366. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 29 records from Biological data measured on water bottle sampels at station AT_II-119/5_29-6. 106 records from Sylter Meerstrandläufer. 572 records from Planktic foraminifera counts of sediment core V04-32. 510 records from Planktic foraminifera counts of sediment core V20-242. 221 records from (Table 1) Distribution of ice-rafted fossils in ODP Hole 104-642B. 7245 records from (Figure 5) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-627B. 10 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 36 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 5294 records from Planktic foraminifera counts of sediment core PS2644-5. 36 records from Liether Park 1 (LMS), Klasse 5b. 95 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC09. 112 records from Total foraminifera counts of multinet M21/5_MSN742. 4 records from Microzooplankton abundance and biomass at station TT054_13-18. 103 records from Plasm bearing foraminifera counts of multinet PO200/6_MSN837. 8 records from Nannofossil abundance of Hole 10-88. 6 records from Nannofossil abundance of Hole 94-609C. 1371 records from Collection Crustacea - ZIM Hamburg. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/045-2. 4 records from Nannofossil abundance of Hole 2-8A. 10 records from Microfossil abundance of Hole 18-173. 8216 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 1012 records from Dinoflagellate cyst species composition of recent surface samples (Appendix). 12612 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 318 records from (Table 2) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Pacific Ocean side). 107631 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 109 records from Planktic foraminifera abundance of Hole 16-161. 6403 records from Planktic foraminifera abundance of Hole 47-397. 30 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 73 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 10695 records from Biological Records Centre - Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1099 records from Fungi collection of the Botanical Museum of the University of Oulu. 1404 records from (Figure 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 93-603B. 9582 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 3702 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 55256 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2000) (AfrOBIS). 99 records from Wiese und Weide am Waldrand von Gusterath. 37 records from Occurrence of mammalia relicts at site Villa Seckendorff. 20 records from Occurrence of mammalia relicts at site Felslindlhöhle. 12 records from Planktic foraminifera abundance of Hole 1-7. 37 records from Range table from planktonic foraminifers in ODP Hole 172-1060A. 61602 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 41 records from Total foraminifera counts of multinet M21/4_MSN714. 7 records from Content of G. menardii in sediment core V25-70. 9 records from Microzooplankton abundance and biomass at station TT043_6-1. 34 records from Nannofossil abundance of Hole 9-84. 33 records from Nannofossil abundance of Hole 49-407. 2 records from Collection Cnidaria - ZSM München. 4127 records from University of Bergen, Gastropoda. 3378 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for DSDP Site 90-594. 214 records from (Appendix C) Analyses of the benthic foraminifer assemblage at ODP Hole 112-679D. 19 records from Description of lithologic section units of IODP Hole 325-M0039A. 24097 records from UF Florida Museum of Natural History Mammals. 49 records from Planktic foraminifera abundance of Hole 73-522A. 57 records from (Table 11) Planktonic foraminifer abundance of ODP Hole 162-987A. 37 records from Siliceous microfossil occurrence, Site 177-1088. 178070 records from The Flora of County Wexford. 21 records from (Table 8) Pleistocene nannofossil range chart for ODP Hole 134-833A. 53 records from (Table 3) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807C. 792 records from (Table 13) Benthic foraminifera in early-mid Miocene sediments of DSDP Hole 90-592. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 140 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 20332 records from Colección del Herbario PSO de la Universidad de Nariño. 238555 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 318 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 84 records from E.C. Manning Park Collection. 4404 records from Planktic Foraminiferal Species Percentages in GeoB1117-2. 61 records from Steinbruch Pluwig. 14 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MARCH-1995-D2. 62 records from Occurrence of mammalia relicts at site Zawalona Cave. 158 records from Planktic foraminifera abundance of Hole 16-155. 5 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 73 records from (Table 17) Calcareous nannofossil occurrences in ODP Hole 130-804C. 188394 records from Vascular Plant Herbarium, Trondheim (TRH). 13028 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Porifera. 1567 records from Whale and Dolphin Conservation Society - WDCS Shorewatch Sightings. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 891 records from National Museum of Marine Biology and Aquarium. 34 records from Borkhart. 122 records from Stever. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 81 records from Schulgarten-St.-Georg-Gymnasium. 13 records from Warnowufer Groß Klein. 14 records from Abundance of Globorotalia menardii of sediment core GeoB2110-3. 38862 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 114 records from Plasm bearing foraminifera counts of multinet SO117_MSN1243. 370 records from Size of planktic foraminifera at CTD station PS55/051. 89 records from (Table 3) Dinoflagellate cysts from sediment profile PS1730. 5 records from Phytoplankton abundance at station Casma_2003-06-24_2, Casma, Peru. 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 1669 records from Fungus herbarium, UiB. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 150 records from Total foraminifera counts of multinet M42/3_MSN1361. 29 records from Counts (1) of calcareous dinocysts along profile Stevns-Klint. 1698 records from MNA Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 2 records from Composition of the larger coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 823 records from Planktic foraminifera counts of sediment core V17-165. 4357 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 117-728A. 44 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE293. 136 records from Calcareous dinocysts from profile Calais-Escalles. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-09-1. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/049-3. 6 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 32 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 56 records from Nanoplankton abundance at station GeoB2021-3. 285 records from (Table 1) Distribution of planktonic foraminifera shells of different species in deposits from DSDP Hole 33-315A. 5 records from The nematoda fauna of sediment samples of Sarso Islands, Red Sea (Table 5). 75 records from Naturpark Kottenforst-Ville 19.6.09. 10 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-14. 120000 records from Elephant Seal Sightings, Macquarie Island. 40619 records from Invertebrate Zoology Division, Yale Peabody Museum. 684 records from Percentages of planktonic foraminifera species in sediment core V23-110. 63952 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 989 records from BÜG. 45 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB02 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 435 records from (Table 4) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-654A. 503 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Invertebrados. 1202 records from (Table 18) Ranges of benthic foraminifers through the Neogene in DSDP Hole 23-219. 12476 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 52 records from UCM Mammal Collection (Arctos). 408 records from Planktic foraminifera abundance of Hole 23-220. 463 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 444 records from Phytoplankton abundance in surface water in May 1996, Ilo, Peru. 12940 records from Oregon State Ichthyology Collection. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 1830 records from National Whale and Dolphin Sightings and Strandings Database. 2257 records from South Western Pacific Regional OBIS Data Asteroid Subset (South Western Paci fic OBIS). 179 records from Planktic foraminifera abundance of Hole 68-502B. 5 records from A new species of Harpactea Bristowe, 1939 from Turkey (Araneae: Dysderidae). 2029 records from Planktic foraminifera abundance of Hole 26-258A. 127 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE6. 266 records from Range table from planktonic foraminifers in ODP Hole 175-1075A. 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 109 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1172D. 48 records from Phytoplankton abundance in surface water in September 1996, Chimbote, Peru. 50 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 13910 records from Lichen Collection - University of Washington Herbarium (WTU). 10819 records from Irish Wetland Birds Survey (I-WeBS) 1994-2001.. 10 records from Two new species of armoured spiders from Vietnam and Cambodia (Araneae: Tetrablemmidae: Pacullinae). 118866 records from European Molecular Biology Laboratory Australian Mirror. 10170 records from Seil Natural History Group - SNHG Biological Records Dataset. 10211 records from USBombus, contemporary survey data of North American bumble bees (Hymenoptera, Apidae, Bombus) distributed in the United States. 4814 records from Carabidae of the Carpathians. 130020 records from Allan Herbarium (CHR). 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 4671 records from Otter in coastal areas - Carcasses. 113 records from Rund um das LUGY. 4076 records from Barrow Island Ants. 94 records from (Appendix 4) Calcareous nannofossils in ODP Hole 113-689B. 21663 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 23215 records from Royal Museum of Central Africa - Albertian Rift Butterflies (ENBI wp13). 43882 records from University of Alberta Vascular Plant Herbarium (ALTA). 12 records from Naturalis Biodiversity Center (NL) - Mammalia. 419508 records from Meadow and Pasture Inventory (SJV). 131 records from Total foraminifera counts from multinet M32/3_MSN956. 84 records from (Table 4) Morphologic variability in the Globorotalia puncticulata group and abundances of dominant species at DSDP Hole 80-548. 174 records from Antarctic pycnogonids. 32 records from (Table 8) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-685A. 1 records from Pollen record of a sediment profile from Lake Nikolay. 247472 records from The Second Atlas of Breeding Birds in Britain and Ireland: 1988-1991. 1620 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 80 records from Förderzentrum Schmölln. 24 records from Nannofossil abundance of Hole 8-72. 48186 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 7595 records from Fish Collection of Natural History Museum and Institute, Chiba. 85 records from Range table from benthic foraminifers in ODP Hole 154-929B. 434 records from (Table 4) Benthic foraminiferal community at DSDP Hole 94-609B. 57 records from Waldhusener Moor (Lübeck-Kücknitz). 64 records from Kabelskebach (Kabelsketal, Saalkreis). 68 records from Plasm bearing foraminifera counts of multinet M21/5_MSN729. 154 records from Total foraminifera counts of multinet M36/6_MSN1197. 2 records from MfN - Fossil plants II. 2 records from Nannofossil abundance of Hole 3-14. 4 records from Ostracoda abundance of Hole 56-435. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-063. 863 records from (Table 2) Distribution chart of dinoflagellate cysts and acritarchs from Angles, Southeast France. 2113 records from Flora de macroalgas del litoral oaxaqueño. 1296 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 879 records from (Table 1) Relative abundance of planktic foraminifera at DSDP Site 48-401 from the Bay of Biscay, North Atlantic. 80 records from Hüttenseepark (Meißendorf). 157 records from Bizzenbachtal (Wehrheim/Taunus). 2 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 23 records from Tümpel Schulbiologiezentrum. 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 13737 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 10 records from Plasm bearing foraminifera counts from multinet M31/2_MSN891. 137 records from Abundance of planktic foraminifera at CTD station PS55/019. 885 records from Phytoplankton abundance during ARGOS cruise Argos90/8. 2392 records from Benthos counted on dredged samples during Valdivia cruise VA44. 2 records from Nannofossil abundance of Hole 74-526C. 313 records from Planktic foraminifera counts of sediment core V29-48. 44 records from Collection Arachnida - ZSRO. 26 records from Nannofossil abundance of Hole 15-151. 9 records from Nannofossil abundance of Hole 26-250. 204 records from Dinoflagellates and pollen of the Brito-Arctic Igneous Province flora, ODP Hole 104-642E. 6 records from Sediment properties of core CD86_11_BC8. 12 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB04 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 26 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 150 records from Planktic foraminifera abundance of Hole 31-299. 746 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 218 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 3 records from Phytoplankton abundance measured on water samples from rivers of the Lena Delta in 2009. 6782 records from Zooplankton Abundance Based on Taxa and Life Stages or Size. 212 records from Am Moosangerweg. 573 records from Macrobenthic species of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 67661 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1994) (AfrOBIS). 148 records from Hintere Halde. 651 records from Planktic foraminifera abundance of Hole 9-78. 28 records from Foraminifera abundance of Hole 86-580. 6 records from Occurrence of mammalia relicts at site Mitoc Malul Galben. 771 records from Planktic foraminifera abundance of Hole 73-522. 18918 records from (Table 1) Distribution of benthic and planktonic foraminifers at DSDP Hole 28-270. 1066 records from Benthic foraminifera abundance of Hole 80-549A. 645 records from Phytoplankton abundance in surface water in March 1997, Ilo, Peru. 4034 records from Collection Aves (bird skins) SMF. 119 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Black Poplar survey. 1020 records from (Appendix A2) Planktonic foraminifera of ODP Hole 159-958A. 11 records from Clubionidae from Laos and Thailand (Arachnida: Araneae). 3 records from Range table from planktonic foraminifers in ODP Hole 151-912C. 18 records from Range table from planktonic foraminifers in ODP Hole 180-1109A. 899 records from KUBI Invertebrate Zoology Collection. 7 records from (List 1) Fossil record of Mollusca in Schleswig-Holstein, Germany. 3 records from A new Costa Rican species of Leptanilloides (Hymenoptera: Formicidae: doryline section: Leptanilloidinae).. 3633 records from Bioimages. 3 records from Diatom abundance of Hole 38-338, Part 2. 324 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 26 records from Schulteich Heinrich-Mann-Schule. 139 records from Total foraminifera counts of multinet M21/1_MSN611. 2749 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 409 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 3 records from Notoraja martinezi sp. nov., a new species of deepwater skate and the first record of the genus Notoraja Ishiyama, 1958 (Rajiformes: Arhynchobatidae) from the eastern Pacific Ocean. 274 records from Detection histories for eight species of Amazona parrots in Venezuela during the NeoMaps bird surveys in 2010. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 219 records from (Table 2) Stratigraphic distribution of planktonic foraminifera from the middle Miocene to upper Miocene in ODP Hole 134-832B. 17 records from Benthic macrofauna abundance of sediment core 13200-073. 42806 records from The census of national forest of Benin .. 338 records from Fundación Miguel Lillo - Colección Criptogámica. 172137 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 314 records from Peces laguna El Tinije. 17618 records from BioGIS - Mammals - INPA database. 71 records from (Data S1) Palynology of ODP Site 113-696. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 8780 records from Artròpodes d'Andorra. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 70416 records from National Bat Database of Ireland. 1 records from Waldtag in und um Seelingstädt. 95 records from BIRDRACE BiBi. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 156 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 6 records from Wiese. 16 records from Coccolith counts of multinet M32/5_MSN986. 21 records from Nannofossil abundance of Hole 6-55. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 558 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_3-CTD37. 4 records from Nannofossil abundance of Hole 9-80A. 36 records from (Table 2) Ostracode distribution in ODP Hole 122-760B. 3950 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 112-682A. 327 records from Elaboración de las fichas técnicas para la evaluación del riesgo de extinción de 18 especies de peces dulceacuícolas mexicanos. 12539 records from Ibaraki Nature Museum,Lichen collection. 22421 records from Natal Museum - Mollusc Collection (AfrOBIS). 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 13 records from FND "Weißer Berg" Leißling. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 126 records from Total foraminifera counts from M35/1_MSN1050. 6698 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 31 records from Nationalpark Harz Schul-AG Braunlage. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 3 records from Nannofossil abundance of Hole 31-301. 3 records from Nannofossil abundance of Hole 94-609A. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 2182 records from Ibaraki Nature Museum, Mollusk collection. 13003 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 15389 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 66709 records from United States National Plant Germplasm System Collection. 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 11 records from Privatteich(St.Leon). 10 records from Plasm bearing foraminifera counts from multinet M31/2_MSN894. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 122 records from Total foraminifera counts of multinet M21/6_MSN785. 11 records from Zoobenthos in surface sediments off Cape Lucul. 49 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 209 records from Relative abundance of coccosphere-units at site GIK23414. 451 records from Nannofossil abundance of Hole 15-148. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 1972 records from (Figure 6) Distribution chart of benthic foraminifers in ODP Site 126-792. 36506 records from Plant Specimens of Kurashiki Museum of Natural History. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 274 records from Foraminifera abundance of sediment core BM1958.631. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 145 records from Whale log - observations from ANARE voyages. 99035 records from Biological Records Centre - Dragonfly and Damselfly (Odonata) records for Britain to 1992, from the former Dragonfly Recording Scheme. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 1691 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 1130 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 3 records from Analyses of the recent components of sediment core PS1215-2. 12832 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 19 records from Occurrence of mammalia relicts at site Gröbern. 68 records from Planktic foraminifera abundance of Hole 22-213. 126 records from Planktic foraminifera abundance of Hole 32-305. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 2 records from Abundance of benthos infauna at station GIK23025-2. 62487 records from Ornitho.eus. 20 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 9421 records from The Orchid Atlas of Western Australia. 875 records from Fish monitoring data in Lake Kasumigaura. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 780 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 3 records from Microfossil abundance of Hole 50-415. 101 records from MVZ Mammal Observations (Arctos). 176729 records from CAS Entomology (ENT). 11 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 61 records from Fürstenberger Ralley Teil 3. 73 records from VFD-HH/SH: Pferdweide Lammert. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 10 records from Benthic macrofauna abundance of sediment core 13078-017. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 164 records from Planktic foraminifera abundance of Hole 22-215. 26 records from Planktic foraminifera abundance of Hole 20-200A. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 268876 records from Fiji Terrestrial Arthropods. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 3512 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 17 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 117 records from Wassermann. 1849 records from National Trust - Heigham Holmes species data held by The National Trust. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 3204 records from Faunal Inventory of Morysin Nature Reserve. 9 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 251760 records from Moths Ireland. 105 records from BIRDRACE coesfelder_vogelkundler. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 110 records from Abundance of planktic foraminifera at CTD station M39/4_366CTD-22. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 87 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 18 records from Meiofauna abundance in sediment core 13368-015. 308 records from Planktic foraminifera counts of sediment core V19-178. 22 records from Phytoplankton abundance at bottle station GOM6/1. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 14473 records from Ontario Breeding Bird Atlas 1981-1985. 14637 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 29 records from Klimaoasen in Köln. 83 records from Planktic foraminifera abundance of Hole 14-135. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 190 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1244-2. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 910 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 1114 records from MEXU/Tipos de plantas vasculares. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 19017 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 5233 records from (Appendix A) Stable carbon and oxygen isotopes and paleoproductivity reconstructions for the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 82641 records from Vascular Plants, Observations, Oslo (O). 257 records from Kernberge und Umgebung (Jena). 46 records from An der Ohm, (Wettsaasen). 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 1 records from Planktic foraminifera abundance of Hole 8-72. 163 records from Planktic foraminifera abundance of Hole 32-313. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 9402 records from MEXU/Plantas Vasculares. 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 1351 records from Neogene palynomorpha from site 93-603, part 1. 2357 records from Foraminifera abundance of Hole 17-167. 525 records from Planktic foraminifera abundance of Hole 94-609. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 216125 records from R. L. McGregor Herbarium Vascular Plants Collection. 12 records from Abundance of epibenthic echinoderms at seafloor photography station M21/5_317. 306 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 15 records from AKG-Bensheim. 12679 records from Mycology Herbarium, Trondheim (TRH). 5241 records from Nordic Genetic Resources. 28 records from Occurrence of mammalia relicts at site Climauti II. 18038 records from Sponges of Rathlin Island. 16695 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 1115906 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 880 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 7 records from Microzooplankton abundance and biomass at station NBP97-03-10-10. 70 records from Exotic terrestrial flatworms, Macquarie Island. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 1. 1494 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 2 records from The Genus Criodion (Audinet-Serville, 1833) (Coleoptera, Cerambycidae): First Record for Panama. 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 211789 records from MVZ Mammal Collection (Arctos). 158052 records from Field Museum of Natural History (Zoology) Mammal Collection. 44 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 1545 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 116639 records from The digitization of plant specimens of NTU. 5 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 1 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 101 records from Birdrace-Herford-Birder-Herford. 35 records from Gym Freyung. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-23-2. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 5 records from Naturschutzgebiet Ahrmündung (Remagen). 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 102 records from Range table from planktonic foraminifers in ODP Hole 169-1035D. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 2233 records from Chrysomelidae of Poland. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 133 records from Total foraminifera counts of multinet PO247/2_MSN1381. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 2 records from Kirchenforst. 115 records from Nannofossil abundance of Hole 29-279A. 21 records from Nannofossil abundance of Hole 24-232A. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 61226 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 33 records from Phytoplankton abundance in surface water in 1998, Ancon, Peru. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 748 records from Moluscos Marinhos de Augusto Nobre. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 2997 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 501 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 61 records from Plant specimens of Hokkaido University Museum. 66 records from Foraminifera abundance of Hole 55-432A. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 899 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 1 records from Results of palynological analysis of Hole 302-M0004C. 3 records from Collection Xiphosura SMF. 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 3 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 5139 records from Herp Collection. 1056 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 53 records from Planktic foraminifera abundance of Hole 29-281A. 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 3191 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 97 records from LauWi. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 9 records from Nannofossil abundance of Hole 60-455. 10454 records from The Erysiphales Collection at the Botanische Staatssammlung München. 406 records from Harpactus Shuckard. 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 241 records from Planktic foraminifera abundance of Hole 67-499B. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 145180 records from Bernice P. Bishop Museum. 2189 records from Algae, Specimens, Agder naturmuseum (KMN). 84521 records from BioGIS - Vascular plants - INPA database. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 388 records from Mooswald (Freiburg). 30 records from Benthic foraminifera abundance of Hole 42-379A. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 1404 records from Arachnologie - SMNG. 2120907 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 6163 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 20 records from Mikroorganismen. 72 records from Faunal assemblage of sediment core TR149-35. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 1471 records from EcoRecord - Bryophyte records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 48 records from Wahner Heide LK 12 Biologie. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 30 records from Nannofossil abundance of Hole 8-71. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 12 records from Ficha de Sonora aemula. 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 939 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 114 records from BIRDRACE VIE will rock you!. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 71 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/367-1. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 64 records from Feuchtbiotop Weidenkaule. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 22 records from Nannofossil abundance of Hole 9-83A. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 271 records from Planktic foraminifera counts of sediment core RC11-147. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 1183 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 3761 records from Mountain Invasion Research Network (MIREN) survey. 22 records from Sediment properties of core PLG95B_06BOXG. 48 records from Freiheitsring (Frechen). 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 8 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 353 records from Colección de Entomología - Arthropoda. 1723 records from KTU Pinophyta. 56 records from Nannofossil abundance of Hole 94-607. 3023 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 7070275 records from Great Backyard Bird Count. 12026 records from Arizona State University Amphibian and Reptile Collection. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 2022 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 90 records from Schulhof Bühlschule Giengen. 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 827 records from ZFMK Sound Archive. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 1305 records from Flora genérica de las gramíneas del estado de Tlaxcala. 131 records from Unser Schulhof - eine Apotheke. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 10400 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 302 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 5 records from Analyses of the recent components of sediment core PS1400-4. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 48 records from Trockenrasen bei Dörndorf. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 292 records from (Table A1) Calcareous nannofossil of the Middle Cenomanian Event in ODP Site 207-1260. 45401 records from Saltabel - Orthoptera in Belgium. 1638 records from (Table 1) Relative abundances of benthonic foraminifera in ODP Site 116-717. 394 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE255. 1403 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-205. 4752 records from (Appendix B5) Distribution of planktic foraminifera in DSDP Site 90-594 east of New Zealand. 138 records from Planktic foraminifera abundance of Hole 26-250A. 71 records from Planktic foraminifera abundance of Hole 2-11A. 5733 records from Small Mammal Research Database. 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 35266 records from Kathryn Kalmbach Herbarium. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 160 records from Wirbach-Taubental (Bad Blankenburg). 103 records from BIRDRACE Die Otzberger. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 12 records from Bilder der Natur. 340689 records from Entomology, Natural History Museum, University of Oslo. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 47 records from Schulgelände Ceciliengymnasium. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 84 records from BIRDRACE Birding for Nature. 32 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 23 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5136-1. 70 records from Parkuntersuchung Weißer See. 6 records from Nannofossil abundance of Hole 7-63. 19 records from Nannofossil abundance of Hole 31-298. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 76 records from Coccoliths in sediment core PS1533-3. 315 records from Planktic foraminifera counts of sediment core RC17-69. 566 records from (Appendix A1) Distribution of benthic foraminifera in ODP Site 184-1143. 43 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV30_1. 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 4826 records from Vascular Plants Collection of National Museum of Nature and Science. 186 records from Total foraminifera counts of multinet M21/1_MSN604. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 7 records from Abundance of nematoda in sediment profile M3/1_029 from the Iberian deep sea basin (Table 5). 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 57 records from Nannofossil abundance in sediment core PS1311-4. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 672 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 97 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 778 records from Planktic foraminifera abundance of Hole 40-362. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 1028826 records from SEAMAP - marine mammals, birds and turtles. 94 records from Coccolith counts of multinet SO119_MSN1298. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 40 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 13750 records from Impetus - Herbarium Hamburgense. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 303 records from (Table 4) Distribution of sphenoliths at DSDP Site 82-563 in the North Atlantic. 32698 records from Fish tag database. 154 records from Planktic foraminifera distribution of sediment core TRI171-27. 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 1 records from Planktic foraminifera abundance of Hole 54-420A. 1582352 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 74 records from SuLaMa reptile monitoring. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 36301 records from Pelagic Fish Observations 1968-1999. 6 records from Sediment properties of core PLG93_BCORE1. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 302 records from Stadtpark Sulzbach-Rosenberg. 168 records from Weidenhüttendorf an der Würm (München). 318 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 774 records from Planktic foraminifera abundance of Hole 80-549A. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 2937 records from Homoptera. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 7 records from Three new Scandinavian species of Culicoides (Culicoides): C. boyi sp. nov., C. selandicus sp. nov. and C. kalix sp. nov. (Diptera: Ceratopogonidae). 6056 records from Lichens of Knyszyn Forest. 10482 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 310 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 2 records from New data on the rare Afrotropical scarab beetles Orphnus drumonti Frolov and Delopleurus naviauxi Frolov et Cambefort (Coleoptera, Scarabaeidae, Orphninae and Scarabaeinae). 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8858 records from (Appendix 2a) Foraminiferal analyses of research borehole Sonder Vium. 184156 records from The Flora of County Waterford. 1200 records from monocotyledonous_geophytes_of_fergana_valley. 588 records from Relative abundance of ostracods in sediment core Lz1120. 107 records from BIRDRACE Herford Birders. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 2 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 12 records from Abundance of radiolaria at station LV28-40-2. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 1 records from Hausgarten. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 14 records from Benthic macrofauna abundance of sediment core 12930-093. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 869 records from Lepidoptera Observations from New Zealand by Donald Hobern. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 528 records from Collection Crustacea - KAUMM. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 1067 records from (Table 6) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 181 records from Collection Crustacea ZMG. 86 records from Fliegenhaupt Marksuhl. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 320 records from Myxomycetes collection of the University of Eastern Finland. 441 records from Pollen analysis of surface samples from Germany and Austria. 24402 records from Ibaraki Nature Museum, Arthropoda collection. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 10269 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 1130 records from Ostracoda in sediment core PS51/154-11. 766 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Peces. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 584 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 88 records from Total foraminifera counts of multinet SO118_MSN1265. 77 records from Total foraminifera counts from M35/1_MSN1075. 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 30890 records from MEXU/Asteraceae. 3 records from CNIN/Mantodea. 175 records from INSECT COLLECTION. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 93 records from Südwestlich der Parkwiesen. 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 99 records from Planktic foraminifera abundance of Hole 94-610E. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 25 records from Benthic foraminifera abundance of Hole 1-4. 1 records from Pollen and spore abundance of Hole 42-379A. 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 107 records from Planktic foraminifera abundance of Hole 18-180. 2 records from Benthic foraminifera abundance of Hole 42-376. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 66 records from Foraminifera species abundances from tow TT007_10-MOC20. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 3 records from Antarctic Arrow worms. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 2723 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 21 records from Meiofauna abundance in sediment core 13077-006. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 81 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 2000 records from (Table A2) Sea surface temperature reconstruction of DSDP Site 94-607 in the North Atlantic. 6 records from UWYMV Herpetology Collection (Arctos). 201 records from Mammals in MZNA-VERT: project CAS. 2839 records from Rocky Shore Macroalgae. 10883 records from RSPB - Swift Inventory of Nest Sites in the UK, 2009 (RSPB and Swift Conservation Groups). 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 1 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 3481 records from Irish National Frog Database. 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 2846 records from Coleoptera, NEF. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 145 records from privater Garten. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 12 records from Abundance of radiolaria at station LV28-44-1. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 256 records from BIRDRACE Upupa epöpse. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 9 records from Microzooplankton abundance and biomass at station TT043_9-1. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 356 records from Biotope in Rheine - Aktion 350. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 9721 records from Birds of Ireland. 5 records from Memorial University Botanical Garden Collection. 107 records from 1st Austrian Birdrace (Wien). 13639 records from Senckenberg - CeDAMar Resource. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 599 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 50 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 144 records from BIRDRACE Punkbirder Helgoland. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-120BX. 2268 records from (Table 1) Distribution of Cretaceous-Tertiary benthic foraminifers in ODP Hole 129-802A. 279 records from Planktic foraminifera abundance of Hole 11-98. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 44 records from Flora und Fauna in unserer Kita. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 177 records from Donauinsel des BN bei Entau. 6 records from Nannofossil abundance of Hole 55-430B. 27 records from (Table 12) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-666A. 1554 records from Biodiversidad de Datura (Solanaceae) en México. 9614 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 76 records from Colección de Entomopatógenos de México (CNRCB). 679 records from Results of palynological analysis of Hole 302-M0004A. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 91 records from Benthic foraminifera abundance of Hole 84-569A. 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 49 records from Collection Thysanoptera SMF. 88 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 53 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 7795 records from Hymenoptera collection, Natural History Museum, University of Oslo. 11 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 52 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 49637 records from Monitoring data from the federal state Hesse (Germany). 153 records from Selztal bei Friesenheim. 57 records from Garten in Schmölln. 18 records from Landschaftsschutzgebiet Buchhorst2. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 25 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_8-CTD93. 24 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 4 records from Estimated plankton abundance at station PS63/064-6. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 194 records from Collection Cnidaria - ZMB. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 1392 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 53606 records from BioMar - LIFE project. 6660 records from Weevils of the Tatra Mts.. 214 records from Binsenwiesen. 87 records from Klütwald. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 122 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 180 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 2088 records from Benthic foraminifera of sediment core MD99-2286. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 454 records from Collection des Mollusques (BOUM). 13624 records from Mammal collection, Natural History Museum, University of Oslo. 5 records from Streuobstwiese (Mittelgasse 4). 347 records from (Table 4) Standing stock values of important species in surface sediments. 33 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 45 records from Nannofossil abundance of Hole 28-265. 38984 records from Herbarium (UNA). 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 96 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 231 records from Gunma Museum of Natural History, Fish Specimen. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 4 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 690 records from Mid Ulster Hare Surveys 2012-2015. 194 records from Colección Herpetológica de la Patagonia. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 120714 records from Arizona State University Lichen Collection. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 1 records from Planktic foraminifera abundance of Hole 8-73. 1042 records from Planktic foraminifera abundance of Hole 37-333. 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 246 records from Benthic foraminifera abundance of Hole 73-524. 8 records from Pollen and spore abundance of Hole 42-380. 493140 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 764 records from BioGIS - Fish - INPA database. 57 records from Occurrence of mammalia relicts at site Moladova V. 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 117 records from Muskox Abundance. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 36384 records from Inventaire National du Patrimoine Naturel : Amphibiens et Reptiles de France (Enquête 1). 118221 records from Mycology herbarium, Oslo (O). 5 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 132 records from Insect (HUNM-IN). 763 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 103322 records from Invertebrates Collection of the Swedish Museum of Natural History. 44 records from Total foraminifera counts of multinet M21/4_MSN721. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 144 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4). 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 12 records from Lepidoptera specimen database of Japan. 129 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 6987 records from National Trust - Ickworth species data held by The National Trust.. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 233 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 133081 records from NINA insect database. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 19741 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 114 records from BIRDRACE Di-Bi-Di-Birder. 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 28498 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 8 records from Krittenhorster Wald (Ostkilver). 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 276 records from Planktic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 3 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 145 records from Phytoplankton abundance at station CD46_0405C#7. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 9572 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 2 records from Nannofossil abundance of Hole 6-49. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 113 records from Collection Hydrozoa - ZMB. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 921 records from Planktic foraminifera counts of sediment core RC14-37. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 23879 records from svalbardflora.net. 262 records from (Appendix 6) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD95-2041. 314 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 134 records from Myriapoda - SMF. 1267 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Coleóptera. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 10930 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 141 records from Schulhof und Anlagensee in Nellingen. 2148 records from Eppingen und Umgebung. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 304538 records from Observational database of Icelandic plants. 193 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 4191 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 296 records from DJH. 6 records from Planktic foraminifera abundance of Hole 23-226. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 86 records from Pollen analysis of sediment core GIK16856-2. 961 records from Spencer Entomological Museum. 269 records from 3. Tag der Artenvielfalt Hockenheim. 76 records from Occurrence of mammalia relicts at site Vindija. 55 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 588 records from NHT flora. 78799 records from natagora-earlybirds. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 53 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 456 records from Range table from benthic foraminifers in ODP Hole 144-873A. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 83 records from North Carolina State Museum of Natural Sciences Fishes Collection. 212 records from (Table T4) Planktonic foraminifera abundance of ODP Site 170-1042 sediments. 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 31375 records from MSB Bird Collection (Arctos). 32 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 278 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 11 records from Observation of birds at station PS14/156 along 49° West. 16331 records from UPCB - Herbário do Departamento de Botânica. 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 1 records from Diatom abundance of Hole 95-613. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 767 records from BioGIS - Bats - Asaf Tsoar database. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 2913 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 27 records from Zwickau- Schwanenteich. 163 records from Tiere und Pflanzen am Pfannenbach. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 145693 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 820426 records from Fauna Atlas N.T.. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 87 records from Total foraminifera counts of trap L2_92_B49. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 5 records from Tuttlinger Tag der Artenvielfalt. 54374 records from Fish Specimens. 32112 records from SBMNH Vertebrate Zoology. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 30 records from Leben auf einer Sturmfläche. 92 records from Plasm bearing foraminifera counts of multinet M26/1_MSN843. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 4 records from Nannofossil abundance of Hole 29-281A. 5862 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 12697 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 18 records from Planktic foraminifera abundance of Hole 32-310. 692 records from Planktic foraminifera abundance of Hole 40-360. 94 records from Planktic foraminifera abundance of Hole 80-550. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 405 records from Collection Graptolithina fossil SMF. 1 records from Abundance of benthos infauna at station GIK23004-3. 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 2991 records from Millenium Seedbank (MSB). 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 86088 records from NINA Vanndata øvrige arter. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 23215 records from rmca-albertine-rift-butterflies. 99 records from Düne am Ulvenberg (Darmstadt). 13 records from Tag der Artenvielfalt am Bruckenwasen. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 11 records from Nannofossil abundance of Hole 6-56B. 14 records from Nannofossil abundance of Hole 85-573. 28 records from Nannofossil abundance of Hole 26-253. 18 records from Meiofauna abundance in sediment core 13200-012. 316 records from Planktic foraminifera counts of sediment core V14-101. 497 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 35 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 190 records from Foraminifera abundance of sediment core MD81-LC07. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 3 records from Analyses of the recent components of sediment core PS1215-2. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 73 records from Planktic foraminifera abundance of Hole 2-11. 759 records from Planktic foraminifera abundance of Hole 47-398D. 70 records from Planktic foraminifera abundance of Hole 84-569A. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 5327 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 878 records from Planktic foraminifera abundance of Hole 84-568. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 24 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 48913 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 281250 records from Quadrige. 25545 records from Formidabel; Belgian Ants Database. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 8 records from Occurrence of mammalia relicts at site Wretton. 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 56741 records from Insect Collection of Taiwan Forestry Research Institute. 661 records from Targeting a portion of central European spider diversity for permanent preservation. 82 records from Foraminifera species abundances from tow TT011_5-MOC63. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 3 records from Nannofossil abundance of Hole 51-417D. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 151 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 1346 records from Percentages of planktonic foraminifera species in sediment core V25-59. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 92 records from Siliceous microfossil occurrence, Site 177-1094. 52 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 372178 records from University of Florida Vertebrate Paleontology. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 32 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 7 records from Additions to the myxobiota of the Åland Islands. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 1 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 4139 records from Marie-Victorin Herbarium (MT) - Bryophytes. 4004 records from Sightings Map of Invasive Plants in Portugal. 20 records from Motzener Tonsee. 244 records from WildesMoor bei Schwabstedt. 161 records from BIRDRACE Nord-Seh-Team. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 16 records from Dinoflagellate cysts of surface sediments. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 144 records from Total foraminifera counts of multinet M21/2_MSN640. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 68 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 44 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 21146 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1379 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 161 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 988 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 221 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 1 records from Microplankton counts and carbon biomass at station TT007_15-CTD160. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 26 records from Ostracoda abundance of Hole 13-132. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 52865 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 59 records from Biological Records Centre - RISC Non-Native Species Records for Muntjac. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 1051 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 264743 records from ArtenFinder. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 642 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 310 records from Lepidoptera collection, NTNU, Trondheim. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 43638 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 76911 records from University of British Columbia Herbarium (UBC) - Algae Collection. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 1432 records from Quaternary benthic foraminifera abundance of Hole 95-612. 940 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 610 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 227 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 45 records from Parcela Permanente en el Pantano Martos. 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 9042 records from Northern Biodiversity Program Coleoptera (2010-2011). 237 records from RSPB - Capercaillie national surveys (SCARABBS). 772 records from Fishes of the Congo River 2010 Expedition. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 1436 records from Cowan Tetrapod Collection - Herpetology. 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 29644 records from Phanerogamic Botanical Collections (S). 96 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 149215 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 31 records from Fundación Miguel Lillo - Colección Invertebrados. 9948 records from Bees of Canada / Gschwendtner property collection. 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 1589 records from Global caridean shrimp fauna. 84 records from BIRDRACE Vogelscheuchen. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 12 records from Distribution of meiobenthos in sediment core M23_134 of the northeastern Atlantic (Table 1). 54 records from Wiese am Unterbecken. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 19516 records from MfN - Fossil invertebrates Ia. 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 556 records from Distribution ashore and breeding places of southern elephant seals (OBIS South America, SOUTHERN OCEAN SUB-NODE). 359 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 155 records from Bergbaufolgelandschaft am Muldestausee. 131 records from Artenvielfalt auf dem Schulgelände. 994 records from (Table 6) Quaternary planktonic foraminifers at DSDP Site 65-483. 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 8407 records from NYSM Birds. 7685 records from European riparian ground beetles. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 2 records from Smear slide analysis of sediment core GeoB7427-2. 104 records from Ross Sea Pycnogonids. 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 14997 records from iziko South African Museum - Fish Collection (AfrOBIS). 23077 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 8981 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 27 records from Benthic foraminifera abundance of Hole 34-320A. 302 records from Range table from benthic foraminifers in ODP Hole 144-874B. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 2117 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 1627 records from The Irish Squirrel Survey 2007. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 228 records from Relative abundance of benthic foraminifera of sediment core GIK13239-1, East Atlantic off Senegal and Gambia (Table 3). 8 records from Abundance of radiolaria at station LV28-29-1. 6 records from Ökosysteme rund um Wedel. 16 records from Nannofossil abundance of Hole 47-398B. 2 records from Nannofossil abundance of Hole 74-526. 66 records from Range table from ostracoda in ODP Hole 151-910D. 29 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 102 records from Ostracod abundance in sediment core Lz1120. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 21447 records from Herbarium de Geo. B. Hinton, México. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 741 records from Planktic foraminifera abundance of Hole 20-200. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 84943 records from Herbarium of Umeå University (UME). 535 records from Benthic foraminifera abundance of Hole 73-522. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 75 records from Range table from nannofossils in ODP Hole 199-1220A. 585 records from (Tab. 4) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hills. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 462 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 4 records from Collection Pantopoda SMF. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1443 records from Odonata of the Congo River 2010 expedition. 112 records from BIRDRACE Gütersloher Gimpel. 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 2227 records from Fundación Miguel Lillo - Colección Ornitológica. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 19 records from Dinoflagellate abundance of Hole 81-553A. 1525 records from The French Collection of Medicago truncatula. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 16040 records from Naturalis Biodiversity Center (NL) - Porifera. 1983 records from Seabird 2000. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 404 records from Greater Manchester Ecology Unit - Water Vole Distribution for Greater Manchester. 3064 records from dec2011. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 5079 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 9088 records from Flora of Słowiński National Park, Poland. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 18353 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 241 records from BIRDRACE RennVögel Münsterland. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 57 records from Schulgarten Janusz-Korczak-Realschule. 2633 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 48 records from Diatom assamblage in samples from sediment trap OG5. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 67 records from Tongrube bei Hettstedt. 1610 records from (Appendix A) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747A. 125 records from (Table 4) Ostracode distribution in ODP Hole 122-764A. 69 records from (Table 3b) Distribution of planktonic foraminiferal tests in sediments from Core NKA-3T. 2814 records from Flora acuática vascular y de zonas inundables del área de protección de flora y fauna Laguna de Términos, Campeche, México. 32479 records from Herbario de la Universidad de Sevilla. 770 records from Nivå Bay species list, Zealand, Denmark. 540 records from (Figure 2a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3209. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 777 records from Planktic foraminifera counts of sediment core RC17-108. 1 records from Antarctic Marine Amoebae. 348999 records from BSBI tetrad data for Ireland. 4094 records from Actualización de la base de datos de crustáceos de la Colección Biológica de la Secretaría de Marina. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 70615 records from Marsh Monitoring Program - Birds. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 11370 records from Distribution of planktic foraminifers of core V22-174. 10577 records from Colección de Sifonápteros del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 1 records from Boraginaceae (Cynoglossum cherangauiense). 340 records from Occurrence of mammalia relicts at site Brillenhöhle. 3 records from Sarcodine counts and carbon biomass at station TT011_2-CTD21. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 45 records from Wasser-Lernort Nettemündung. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 15 records from Herdengelhoehle taxa and datings. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 7 records from Range table from planktonic foraminifers in ODP Hole 192-1185B. 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 1 records from Abundance of benthos infauna at station GIK23062-2. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 246 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 24 records from Occurrence of mammalia relicts at site Overmere. 520 records from Planktic foraminifera abundance of Hole 39-357. 44 records from Planktic foraminifera abundance of Hole 19-188. 2083 records from Planktic foraminifera abundance of Hole 72-517. 102 records from Benthic foraminifera abundance of Hole 42-372. 1 records from Microfossil abundance of Hole 42-378. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 428 records from EAN - Herbário Jaime Coelho de Moraes. 19 records from Revision and phylogeny of the Caribbean weevil genus Apotomoderes Dejean, 1834 (Coleoptera, Curculionidae, Entiminae). 10902 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 8717 records from CHAS Mammalogy Collection (Arctos). 147 records from NABU-Auerochsenweide. 100 records from Birdrace-The_Ringers-Friesland. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 112 records from Total foraminifera counts of multinet M11/1_MSN526. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_236-1. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 96 records from Birdrace-federleser-Herford. 57 records from Heidesee / Halle. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 40 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 1122 records from ZFMK DORSA. 212 records from Nanoplankton abundance at station GeoB2017-1. 180 records from Range table from ostracoda in ODP Hole 144-871A. 5732 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 1537 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 108-657A. 355 records from (Table A3) Semi-quantitative frequency of Globorotalia menardii in core SO164-17-2. 38331 records from Botanical Museum, Copenhagen, Mycology Herbarium. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 349 records from Planktic foraminifera counts of sediment core V20-170. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 116 records from (Table 17) Distribution of planktonic foraminifers in ODP Hole 108-668B. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 438 records from (Table 4) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-709A. 845 records from Estudio comparativo del zooplancton en dos regiones de México. 4542 records from Ibaraki Nature Museum, Algae collection. 71586 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 777 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 20626 records from BC Coastal Waterbird Survey. 70467 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 2141877 records from Biologiezentrum Linz. 35345 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 8547 records from Individual Sightings. 5860 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 3224 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 42 records from Foraminifera abundance of Hole 24-236. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 498 records from Dinoflagellate abundance of Hole 94-611C. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 379 records from UAM Herpetology Collection (Arctos). 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 5128 records from Spider Mites Collection of Jean Gutierrez. 39424 records from Irish vascular plant data 1999-2009. 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 14165 records from Entomology at ZMUC, Natural History Musem of Denmark. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 294 records from Naturgarten Langenholtensen. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 12697 records from MVZ Egg and Nest Collection (Arctos). 16 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 1 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 148 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 140273 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 574 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 236 records from GENT Lactarius Deliciosi. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 172 records from Foraminifera abundance of Hole 59-448A. 2032 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 8305 records from Collection Bryozoa SMF. 139 records from Siliceous microfossil occurrence, Site 177-1093. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 1997 records from Aves de la cuenca media del río Bogotá. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 7 records from Nannofossil abundance of Hole 38-336. 36 records from Nannofossil abundance of Hole 14-141. 596 records from Planktic foraminifera counts of sediment core A15-558. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 115 records from (Table 2a) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Canary upwelling. 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 169 records from Planktic foraminifera counts at CTD station PS55/051. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 135 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 6 records from Nannofossil abundance of Hole 6-49. 753 records from Planktic foraminifera counts of sediment core V28-127. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 91 records from BIRDRACE SchrägeVögel. 76 records from Faunal assemblage of sediment core GS7603-10. 171 records from Total foraminifera counts of multinet M42/3_MSN1370. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 9 records from Nannofossil abundance of Hole 1-2. 591 records from Planktic foraminifera counts of sediment core V16-25. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 2184 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 82736 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 10116 records from CUMV Mammal Collection (Arctos). 704 records from Planktic foraminifera counts of sediment core V18-207. 797 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV23. 2321 records from CeDoc de Biodiversitat Vegetal: BCN-Phycophyta. 191 records from Foraminifera abundance of sediment core C1960.202. 1 records from Occurrence of mammalia relicts at site Ejstrup. 1159 records from Countryside Council for Wales - Bat Roosts Database - North East Wales. 59 records from Schulteich Freie Waldorfschule Darmstadt. 171 records from Sahrbachtal Kreis Ahrweiler. 4 records from Nannofossil abundance of Hole 55-430A. 264 records from Planktic foraminifera counts of sediment core RC12-339. 3382 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 62 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 49 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 12 records from Early succession in benthic hard bottom communities in Kongsfjorden, Svalbard - abundance. 35 records from Nannofossil abundance of Hole 78-543. 2020 records from Bryophyte collection of Jyväskylä University Museum. 1023 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 7501 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 75444 records from Royal Botanic Garden Edinburgh Herbarium (E). 10075 records from Nematoda of Costa Rica (INBio). 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 65529 records from CAS Ornithology (ORN). 3 records from Blankenfelder See. 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 8 records from Nannofossil abundance of Hole 49-409. 2730 records from (Table 10) Distribution of planktonic foraminifera in the middle to late Miocene section of ODP Hole 149-900A. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 50 records from Planktic foraminifera abundance of Hole 60-457. 1 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2029 records from National Trust - Sutton Hoo species data held by The National Trust.. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 97 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 168 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 477 records from EASIANET. 19 records from Microplankton data off Mejillones, 2006, Chile. 371 records from Planktic foraminifera abundance of Hole 63-470. 36 records from Range table from planktonic foraminifers in ODP Hole 144-877A. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 681 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 276 records from Environment Agency - Crayfish data update for Environment Agency Thames Region March 2009. 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 11964 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 3161 records from Distribution of foraminifera of sediment core ENAM93-21. 143 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 84 records from Benthic foraminifera abundance of Hole 84-566C. 13 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (verified). 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 39 records from Red list project inventory, fungi. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 1101 records from Relative abundance of ostracods in sediment core Co1202. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 1298 records from Planktic foraminifera abundance of Hole 23-219. 38 records from Microfossil abundance of Hole 21-206C. 1 records from Dinoflagellate abundance of Hole 19-183. 13593 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 8100 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 162042 records from KU Museum of Invertebrate Paleontology. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 8566 records from CRI - Herbário Pe. Dr. Raulino Reitz. 173678 records from Mammalogy Collection - Royal Ontario Museum. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 18703 records from Endemic plants of the Congo basin. 17 records from Hazel Dormouse in Ireland. 46685 records from Tasmanian Museum and Art Gallery provider for OZCAM. 75985 records from Irish Vascular Plant Data - Paul Green. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 85 records from Birdrace-Die_Paradiesvögel-Herford. 43 records from Schulgelände Thurmair-Gymnasium. 65 records from BIRDRACE Federal Birds of Investigation FBI. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 16075 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 16 records from Nannofossil abundance of Hole 9-77B. 260 records from Range table from ostracoda in ODP Hole 144-873B. 44 records from Distribution of late Neogene age calcareous nannofossils in ODP Hole 111-677A (Table 2). 95 records from Vielfalt verschiedener Wiesen. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 12 records from Nannofossil abundance of Hole 20-200. 129 records from Nannofossil abundance of Hole 29-284. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 504 records from Schatzinsel Wangerooge. 248 records from Schulgarten der Volksschule. 33 records from Schüler erforschen die Helme-Aue. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 85422 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 495 records from Life Science National Tsing Hua University. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 21 records from Collection Ctenophora SMF. 27847 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 2387 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 1092 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 68077 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 7 records from Analyses of the recent components of sediment core PS1219-1. 1312 records from GEO-Hauptveranstaltung (Insel Vilm). 15 records from Occurrence of mammalia relicts at site Dendermonde. 186 records from Planktic foraminifera abundance of Hole 94-610. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 14941 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 8523 records from Distribution of planktic foraminifers of core RC24-16. 1406 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 336 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 239 records from Naturerlebnisraum Koppelsberg. 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 59304 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 6 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 750647 records from Museum of Comparative Zoology, Harvard University. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 1346 records from Weevils of Poland. 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 262 records from Speothos Venaticus por Guillermo Gil. 4728 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 19756 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 3 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 541 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 233 records from Föhrenried (Fronreute und Baindt). 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_2-CTD16. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 3 records from Nannofossil abundance of Hole 22-212. 15 records from Microfossil abundance of Hole 59-450. 783 records from Phytoplankton abundance in surface water during cruise CD61. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 5 records from Schulwald Regionale Schule Sprendlingen. 77 records from Occurrence of recent nannoplankton in sediment core M1_MULT242, Arabian Sea (Fig. 2). 9 records from Coccolith counts of multinet M32/5_MSN982. 7 records from Nannofossil abundance of Hole 5-33. 14 records from Nannofossil abundance of Hole 8-72A. 7 records from Nannofossil abundance of Hole 9-82A. 4 records from Nannofossil abundance of Hole 52-418. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 5 records from Nannofossil abundance of Hole 84-569. 249 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 41 records from Altholzparzelle Eilenriede Hannover. 164 records from Planktic foraminifera abundance of Hole 94-610B. 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 135 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 662 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 133 records from Total foraminifera counts of multinet M21/3_MSN676. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 703 records from Planktic foraminifera counts of sediment core V25-59. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 6493 records from UWBM Herpetology Collection (Arctos). 1008 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-196. 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 14 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 415 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 593 records from Ostracoda in sediment core PS51/159-10. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 3450 records from Fishes in MZNA-VERT: ecological assessment of the Aragon river in Sangüesa (Spain). 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 308 records from Wangerooge. 2478 records from (Figure 3) Range charts of selected dinoflagellate cysts in ODP Hole 122-762C. 896 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 2069 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 14602 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 4710 records from Lyman Entomological Museum. 351 records from Great Lakes Forestry Centre Insect Collection. 354 records from Foraminifera distribution of sediment core KS310. 125 records from Artenbestimmung. 325 records from Planktic foraminifera abundance of Hole 32-305. 24 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 176153 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 439 records from Antarctic and Subantarctic Asteroid zoogeography (SCAR-MarBIN: Antarctic OBIS). 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 76 records from The Ants of Bulgaria. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 353 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 576 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 1249 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 1254 records from Registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 77 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2009. 157035 records from The Himalayan Uplands Plant database (HUP Version 1). 40550 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 14693 records from The Gordon Alexander Orthoptera Collection. 3 records from Planktic foraminifera abundance of Hole 54-424B. 94 records from Planktic foraminifera abundance of Hole 32-310. 10 records from Range table from planktonic foraminifers in ODP Hole 169-1038A. 19 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 1957 records from BioGIS - Marine snails - HUJ collections. 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 3406 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 34 records from Order Araneae. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 5238 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 2 records from Nannofossil abundance of Hole 29-280A. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 224 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 56 records from Estetal (Buxtehude). 15 records from Kühnauer Aue und Kühnauer See. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 80 records from BB-Biodiversität b. 238 records from Coccoliths in ODP Hole 104-643A. 410 records from (Appendix 3) Planktonic foraminiferal composition from ODP Site 172-1056. 143 records from Akita Prefectural Museum＋Malacostracans Specimens of Akita Prefectural Museum. 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 3633 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 233 records from Total foraminifera counts from M35/1_MSN1044. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 149 records from Bayerische Donau - Neu Ulm. 3 records from Nannofossil abundance of Hole 9-80. 32 records from Nannofossil abundance of Hole 67-499. 149 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 353 records from Stadtgebiet (Dannenberg). 16 records from Abundance of radiolaria at station LV28-3-3. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 1015 records from Irish Marine Turtle Database. 28 records from Stadtpark Prinzengarten (Sigmaringen). 10 records from Microzooplankton abundance and biomass at station TT043_21-22. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 531415 records from Swiss National Butterflies Databank. 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 1377 records from Red list project inventory, lichens. 316 records from Planktic foraminifera counts of sediment core RC11-86. 317 records from Planktic foraminifera counts of sediment core RC14-29. 35 records from Ortsrand Zandershagen. 45 records from Antarctic Isopods. 5 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 12 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 2074 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 4256 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 32468 records from MedOBIS (EurOBIS). 500808 records from Neptune Deep-Sea Microfossil Occurrence Database. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 29 records from Occurrence of mammalia relicts at site la Grotte du Thai. 97 records from Occurrence of mammalia relicts at site Rejtek 1. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 1474 records from Herbarium Rhoenmuseum Fladungen. 2 records from Nannofossil abundance of Hole 7-64A. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 7 records from Megafauna biomass in surface sediment during cruise PLG95A. 691 records from RSPB - Black grouse national surveys (SCARABBS). 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 34341 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 36 records from Occurrence of mammalia relicts at site Trebacki krs. 7 records from Range table from planktonic foraminifers in ODP Hole 182-1132A. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 60 records from Planktic foraminifera abundance of Hole 19-192. 2238 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 161910 records from UA Herbarium. 2182 records from Plantlife International - Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 3 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 135 records from Waldi-Weiher. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 19121 records from Biological Records Centre - Cerambycidae Dataset. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 100 records from Grenzturm Hohen Neuendorf. 180 records from Paul-Gerhardt-Schule Dassel. 89 records from Birdrace-Team_Wangerooge-Friesland. 40 records from Tiere und Pflanzen um uns herum !. 5 records from Fledermäuse u. nachtaktive Insekten. 269 records from BIRDRACE Dithmarscher Deichhühner. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 85 records from Sedimentological investigation on core V25-45. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 3 records from Sarcodine counts and carbon biomass at station TT011_15-CTD168. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 16 records from Lepidurus arcticus survey Northeast Greenland 2013. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 23 records from Landwehrbach. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 122 records from Phytoplankton abundance at station CD46_1005C#4. 7 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 482 records from Kühmark bei Wetzlar. 185 records from Abundance of coccosphere-units of site GIK23414. 31 records from Nannofossil abundance of Hole 4-23. 49 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 1004 records from Arctic soft-sediment macrobenthos (EurOBIS). 2644 records from Invertebrates compiled by W.Block. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 48 records from Benthic foraminifera abundance of Hole 42-380A. 892 records from Weevils of Wales and England. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 1236 records from Percentages of planktonic foraminifera species in sediment core V30-40. 92 records from Nottekanal, Klasse 7 - 10. 58 records from Lüner Holz (Lüneburg). 203 records from Planktic foraminifera abundance of Hole 72-515B. 525 records from Benthic foraminifera abundance of Hole 40-360. 707 records from Benthic foraminiferal assemblages of Upper Cretaceous sediments from DSDP Hole 74-527 in the Angola Basin, South Atlantic Ocean (Table I, Appendix II). 1636 records from Biodiversity of Antarctic Zoobenthos (SCAR-MarBIN: Antarctic OBIS). 10 records from A new species and new records of Hentzia (Araneae: Salticidae: Dendryphantinae) from the United States. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 223320 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 7034 records from Mollusca collection of National Museum of Nature and Science. 1208 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 12 records from Art´n Vielfalt im Kinderwald. 198 records from Total foraminifera counts from M35/1_MSN1047. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 7 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 69 records from Mönchspark. 90 records from Planktic foraminifera counts of sediment core RC13-158. 31 records from Bayerische Donau - Tapfheim. 234 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 2. 8 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 10744 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 5996 records from HRCB - Herbário Rioclarense. 3884 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 3081 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 7470 records from National Taiwan University. 181 records from Alien Species in Poland - Animals. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 20 records from Nannofossil abundance of Hole 7-63A. 10 records from Benthic macrofauna abundance of sediment core 12930-059. 63 records from Planktic foraminifera counts of sediment core V19-21. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 1128 records from Southern Ocean Ostracoda (except Halocypridina). 2 records from Chaetognatha - SMF. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 35832 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 7551382 records from BirdLife Australia, Birdata. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 60 records from Schafsweide Seniorenhaus Berghof. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 61 records from BIRDRACE Baumläufer. 76 records from BIRDRACE Nachtigallen. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 567 records from Collection of Hymenoptera. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 483 records from Artenvielfalt im Rhein-Neckar-Raum. 4 records from Nannofossil abundance of Hole 16-156. 72 records from (Table 5) Distribution of nannofossils in DSDP Hole 87-583F. 14 records from Nannofossil abundance of Hole 14-140. 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 21 records from (Figure 6) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-540. 27 records from Pollen data of trap CB3. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 4915 records from UCM Bird Collection (Arctos). 106 records from Arteninventar rund um den Rannahof. 27 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 81 records from Foraminifera species abundances from tow TT011_6-MOC65. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_8-CTD102. 6 records from Microplankton counts and carbon biomass at station TT012_5-CTD35. 10 records from Zoobenthos in surface sediments during Professor Vodyanitskiy cruise PV32. 1294 records from MfN - Fossil vertebrates III. 92 records from Nannofossil abundance of Hole 31-296. 7 records from Nannofossil abundance of Hole 27-259. 4 records from Range table from nannofossils in ODP Hole 139-857A. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/466-2. 501 records from EcoRecord - Mayfly (Ephemeroptera) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 296 records from (Appendix 1c) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber from MIS 11 of sediment core GeoTu_SL096. 429 records from Larval fish at Helgoland Roads in 2004. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 7811 records from Institut Botanic de Barcelona, BC-Histórico. 122 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 5 records from Analyses of the recent components of sediment core PS1216-1. 2630 records from Planktic foraminifera abundance of Hole 68-502A. 786 records from Planktic foraminifera abundance of Hole 72-518. 30028 records from Natural History Museum, University of Tartu. 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 35 records from Range table from planktonic foraminifers in ODP Hole 180-1112A. 3466 records from (Table 3) Distribution of benthic foraminifers at DSDP Hole 21-206. 288 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 1404 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part III. 19 records from (Table 1) Planktonic foraminifer abundance and stable isotope ratios of a sediment core near Baddeckenstedt, north Germany. 137 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 1046 records from (Appendix Table 4) Number of planktonic foraminiferal specimens within species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 20 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area II. 226 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 23 records from (Table 3) Neogene relative abundances of Uvigerina spp. at DSDP Hole 95-613. 111545 records from Highland Biological Recording Group - HBRG Insects Dataset. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 873 records from Kartlegging av spredning av fremmede bartrær. 56 records from Zitadelle Berlin-Spandau (7b). 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 44 records from Total foraminifera counts of multinet M27/2_MSN879. 7924 records from Dinoflagellate cysts in surface sediments. 39 records from Calcareous dinocysts along profile Ruegen. 3 records from Sarcodine counts and carbon biomass at station TT011_9-CTD115. 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 468 records from Range table from planktonic foraminifers in ODP Hole 155-932A. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 181 records from Nematode abundance of the Eastern Mediterranean Sea in cold seep sediments collected during MSM13/3 and MSM 13/4 cruises (2009). 15 records from Urwald 2 (Bad Waldsee). 54 records from Biotope im Schulumfeld. 159 records from Total foraminifera counts of multinet SO118_MSN1251. 27 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5121-1. 22 records from Phytoplankton abundance at bottle station GOM1/6. 107 records from Bases de datos de Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 804 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 23 records from Benthic foraminifera abundance of Hole 93-603. 65079 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 16 records from MVZ Herp Observations (Arctos). 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 124 records from Range table from benthic foraminifers in ODP Hole 189-1171A. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 87143 records from Sheffield Bird Study Group - Sheffield Bird Study Group (Yorkshire records). 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 57 records from Schulgarten Fichteschule. 18750 records from National Trust - Hatfield Forest species data held by The National Trust.. 18 records from Smear slide analysis on sediment core GeoB4206-1. 13 records from Benthic macrofauna abundance of sediment core 12930-065. 137 records from Planktic foraminifera counts of sediment core V28-25. 479 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P5. 465 records from Philosophenwald und Wieseckaue in Gießen. 145 records from Microplankton abundance in the euphotic zone of the Levantine Sea in October-November 1991. 327 records from Foraminifera abundance of Hole 58-443. 751 records from Planktic foraminifera abundance of Hole 49-408. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 10 records from Oberservation of birds at station PS14/143 along 49° West. 20 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 10 records from (Figure 9) Relative abundance of nannoliths at DSDP Hole 62-465A. 1641 records from Arácnidos de Centroamérica. 1197 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 38 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto75-83. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 61002 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 232 records from Distribution of planktic foraminifera of sediment trap OG5. 14 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT243, Arabian Sea (Fig. 2). 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 12 records from Nannofossil abundance of Hole 74-528A. 22 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 57 records from Kindervilla Aussengelände/ Hiltroper Park. 2 records from Nannofossil abundance of Hole 18-174A. 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 3953 records from Colección de Ostrácodos Recientes del Sur del Golfo de México (ICMyL-DF, UNAM). 492 records from Pliocene/Pleistocene benthic foraminiferal abundances from hole KR9912PC4. 19 records from Pollen record from Mamontovy Klyk. 79 records from Umgebung von Schorndorf. 1059 records from Planktic foraminifera abundance of Hole 15-148. 3 records from Dinoflagellate abundance of Hole 85-572. 3093 records from Biological Records Centre - Mosquito Recording Scheme. 410 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part II. 89 records from Genética y taxonomía de los robalos (Centropomus spp) del golfo de California, México. 2320 records from (Table 7) Distribution of planktonic foraminifera in the early Miocene to late Pliocene section of ODP Hole 149-899A. 23 records from AlgaTerraMovies. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 19 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-139BX. 376 records from Wupperaue bei Kemna (Wuppertal). 651 records from Range table from planktonic foraminifers in ODP Hole 155-940A. 1763 records from Arachnida of Costa Rica (INBio). 5962 records from Broadland Environmental Services Limited - Reptile distribution within Broadland (2004-2011): based upon field signs and sightings. 15996 records from UFP - Herbário UFP - Geraldo Mariz. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 84 records from BIRDRACE Avinauten. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 349 records from Range table from planktonic foraminifers in ODP Hole 182-1126B. 13 records from Foraminifera abundance of Hole 57-438B. 710 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 1013 records from Planktic foraminifera counts of sediment core RE5-034. 475 records from Herp specimens. 638 records from Geochemistry and sedimentology on core PO200/10_21-1. 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 347 records from Planktic foraminifera abundance of Hole 21-209. 500 records from Foraminifera abundance of Hole 48-404. 5 records from Range table from planktonic foraminifers in ODP Hole 178-1103A. 8 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 89 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 9420 records from Sussex Biodiversity Record Centre - Sussex Bryophyte Atlas Data edited by Howard Matcham. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 188 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 3669 records from ARKO strandeng. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639. 13 records from CNAN/Pseudoscorpiones. 173 records from (Table T3) Stable isotope ratios and abundances of foraminifera from ODP Hole 172-1063D. 28 records from (Table A) Wet weight night biomass of dominant mesozooplankton groups obtained from night catches within the Bismark Polygon in June 2001 and June-August 2002. 1658 records from MISE Project Waterford Otter Records, 2011-2015. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 160 records from Total foraminifera counts of multinet M21/1_MSN607. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN658. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1010-1. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 95 records from Total foraminifera counts from multinet M31/2_MSN896. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1. 2733 records from Anfibios y reptiles del estado de Querétaro. 41915 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 321 records from Fuldaaue (Stadtgebiet Fulda). 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 3489 records from Polish seed gene bank – historical passport data of accessions. 137 records from Planktic foraminifera counts at CTD station PS55/077-1. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 521 records from Bayerische Donau - Leipheim. 7341 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD85. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 983 records from (Table 2) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-747A. 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-17-7. 2 records from Nannofossil abundance of Hole 10-87. 526 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 661 records from Ictiofauna de la Bahía de Banderas Nayarit, Jalisco y zonas adyacentes, México. 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 3 records from Planktic foraminifera abundance of Hole 54-419. 3763 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 2190 records from JOI - Herbário Joinvillea. 66 records from Abundance of radiolaria in surface sediment, Sea of Okhotsk. 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 4 records from Zwischen Enz und Schule. 43 records from (Table 5) Distribution of calcareous nannofossils in DSDP Holes 92-600C and 92-601. 17 records from Coccoliths in sediment core PS1527-2. 18 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part I. 185 records from (Table 2) Abundances of dinoflagellates in ODP Hole 105-646B. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 236 records from Los peces del área oaxaqueña de la Reserva de la Biosfera Tehuacán-Cuicatlán. 1972 records from Biodiversidad de los crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas. 2694 records from Recuento de la diversidad florística de Veracruz. 16232 records from Birds Specimens. 6113 records from Hongos del estado de Veracruz. 14 records from Description of lithologic section units of IODP Hole 325-M0047A. 8064 records from Vascular Plants Collection of Sagamihara City Museum. 1017 records from Planktic foraminifera abundance of Hole 26-253. 133 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 1571 records from Diptera, NEF. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 63 records from IWDG Ship Surveys Sightings - Heritage Council Surveys 2004. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 80 records from Total foraminifera counts of multinet M12/3_MSN543. 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 73 records from Tiergarten (Zeitz). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 1 records from Occurrence of mammalia relicts at site Egtved. 5 records from Occurrence of mammalia relicts at site Victoria Cave. 284699 records from Balfour-Browne Club - Water Beetle Surveys from Britain and Ireland. 3786 records from Faun. 765 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 107 records from Hypogean Crustacea of Ireland. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 1360 records from (Appendix table DR1) Foraminiferal distribution data for ODP Hole 178-1098B. 2 records from Nannofossil abundance of Hole 74-525A. 130 records from Planktic foraminifera counts of sediment core RC11-120. 8 records from Component analysis of TV-guided grab sampler GeoB10071-4. 884 records from Percentages of planktonic foraminifera species in sediment core EN066-10PG. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 2 records from Occurrence of mammalia relicts at site Condover. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 11 records from Microzooplankton abundance and biomass at station TT050_21-13. 876 records from Range table from planktonic foraminifers in ODP Hole 138-847B. 59 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 88 records from (Figure 5) Distribution and relative abundances of microbiota recovered from the Jurassic section of DSDP Hole 79-547B. 778 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species: Great crested newts. 1120 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 2 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 1742 records from Eggs Specimen. 3330 records from Collection botanique Le Grand A. (BOUM). 103 records from Birdrace-Die_Nachtigallen-Herford. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 94 records from Total foraminifera counts of multinet M21/4_MSN697. 115 records from Total foraminifera counts of multinet PO247/2_MSN1382. 6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 9955 records from Benthic foraminifera abundance in counts of Hole PRAD1-2. 12 records from Distribution of meiobenthos in sediment core M19_229-2 of the northeastern Atlantic (Table 1). 121 records from Relative abundance of radiolaria in surface sediments. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_8-CTD102. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 88 records from Total foraminifera counts of trap L2_92_A43. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_240-4. 34 records from Relative abundance of coccosphere-units of sediment core GIK23071-3. 3440 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-112BX. 81 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 24 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB02 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB6. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 3 records from Sarcodine counts and carbon biomass at station TT007_3-CTD29. 9 records from Phytoplankton abundance at station Casma_2003-06-04_2, Casma, Peru. 279 records from Koleopterologen am Bausenberg. 2 records from Nannofossil abundance of Hole 66-488. 214 records from Planktic foraminifera counts of sediment core V27-86. 6723 records from NOAA HML Tidal Creek Database. 221 records from Foraminifera abundance of sediment core IN68-5. 354 records from Microfossil abundance of Hole 35-323. 72 records from Occurrence of nannoplankton observed in Early Pliocene samples from Zanclean stratotype of Capo Rossello, Sicily (Table I). 262 records from Coiling ratios of Pulleniatina spp. in sediments from DSDP Hole 16-157. 142 records from Ostracoda in sediment core PS51/135-4. 1848 records from (Table 3) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 325 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 115-708A. 137 records from Corvids Literature Database. 2910 records from The Erysiphales Collection at the University Halle-Wittenberg. 628 records from Relative abundance of planktic foraminifera in sediment core TR126-29 from the 120 kyr time slice reconstruction. 51 records from Taxonomic revision of the spider family Penestomidae (Araneae, Entelegynae). 101 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 1137 records from Planktic foraminifera abundance of Hole 72-516F. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 9866 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 124 records from Total foraminifera counts of multinet M21/1_MSN620. 50 records from Flora und Fauna im Brexbachtal. 181 records from (Table 3) Range chart of calcareous nannofossils in ODP Hole 122-763B. 2087 records from Range table from planktonic foraminifers in ODP Hole 144-871A. 4021 records from (Figure 7) Distribution of benthic foraminifers in the Oligocene to upper Miocene DSDP of Hole 71-513A. 315 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 6229 records from (Table 9) Percentages of planktonic foraminiferal taxa from Site GIK17940. 54856 records from Colección de Referencia de Lepidópteros Diurnos Mexicanos de la CNIN (Lepidoptera: Papilionoidea) (IBUNAM). 3027 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 35 records from Range table from planktonic foraminifers in ODP Hole 144-873A. 14 records from Range table from benthic foraminifers in ODP Hole 178-1101A. 11 records from Oberservation of birds at station PS14/145 along 49° West. 20367 records from R. L. McGregor Herbarium Lichen Collection. 400 records from Distribution of planktonic foraminifera in Oligocene-Miocene of three drill sites from the netherlands Peel area. 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 1045 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4251 records from Aves de la cuenca media del río Chambery, Caldas. 158209 records from All Ireland Non-Marine Molluscan Database. 566 records from NRM-Herpetology. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 94 records from Total foraminifera counts of multinet PO231/3_MSN1333. 2 records from Microzooplankton abundance and biomass at station TT050_15-3. 16 records from Nannofossil abundance of Hole 24-235. 23 records from 2. Aspacher GEO-Tag der Artenvielfalt. 78 records from Planktic foraminifera abundance of Hole 22-212. 72 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 8933 records from National Invasive Species Database. 8169 records from NCSM Mammals Collection. 40 records from (Table T1) Kerogen and organic constituents in ODP Hole 183-1138A, Kerguelen Plateau. 3939 records from Census of plant species in Pahou forest reserve. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 204 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB1710-3. 448 records from Geometry of coccolith Gephyrocapsa in sediment core GIK23062-1. 10 records from (Table 3) Minerals and components of sediments from DSDP Site 94-609_Site, North Atlantic. 4007 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 212 records from Colección nacional de palmas de Colombia - JBQ. 1 records from New sighting of the endangered species blackchin guitarfish, Rhinobatos cemiculus, in the South Aegean Sea. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 6 records from Fließgewässeruntersuchung am Haselbach. 194 records from Bodenteicher Seewiesen. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 21 records from Vogelwelt im Europa-Rosarium. 23 records from (Table 4) Relative abundance of the major nannofossil groups in the Lower Cretaceous of ODP Hole 113-693A. 1763 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 9942 records from Universität Salzburg. 230 records from Range table from benthic foraminifera in ODP Hole 199-1220B. 146 records from Total foraminifera counts from multinet M31/2_MSN891. 153 records from (Table 2b) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Benguela upwelling. 125271 records from Atlantic Reference Centre (OBIS Canada). 650 records from Relative abundance of planktic foraminifera in sediment core K708-001. 7 records from Analyses of the recent components of sediment core PS1402-2. 654 records from Benthic foraminifera abundance of Hole 56-435. 3789 records from TEPB - Herbário Graziela Barroso. 495749 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 65 records from LSG "Großes Bruch". 95 records from BIRDRACE accipiter hardcore birding. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 8 records from Nannofossil abundance of Hole 49-412A. 4719 records from IBF Monitoring of Lichens. 11333 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. UADY_SNIB. 12 records from Microplankton abundance at bottle station SEPT-1999-K7. 262 records from Planktic foraminifera abundance of Hole 1-3. 182 records from Planktic foraminifera abundance of Hole 28-264A. 282 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 1131 records from (Appendix A1) Abundances of planktonic and benthic foraminifera in the Turonian to Coniacian sediments of ODP Site 207-1259. 3477 records from Aves laguna El Tinije. 2 records from Radiolaria assemblage in sediment core GIK23400-3. 574 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 589 records from (Table 12) Distribution of benthic foraminifera in bottom sediments of the Lazarev Sea. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 56 records from Total foraminifera counts of multinet M21/5_MSN741. 139 records from Total foraminifera counts of multinet M42/3_MSN1364. 1 records from FTEA. 5 records from Nannofossil abundance of Hole 34-320A. 2 records from Nannofossil abundance of Hole 3-20C. 3 records from Akita Prefectural Museum＋Echiurans Specimens of Akita Prefectural Museum. 1 records from Description of lithologic section units of IODP Hole 325-M0052C. 561254 records from Dani
Keywords: GBIF; biodiversity; species occurrences